Manajemen Pembelajaran Bahasa Inggris dalam Meningkatkan Hasil Belajar Siswa saat Pandemi Covid-19 di SMA Muhammadiyah 3 Yogyakarta - Mashuri Mashuri; Enung Hasanah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
The purpose of this study was to determine the effectiveness of distance learning during the Covid-19 pandemic in the management of English learning and to improve student achievement at SMA Muhammadiyah 3 Yogyakarta. The research approach used is descriptive qualitative, with data collection techniques through interviews and observations. The research subjects were English teachers and deputy principals of SMA Muhammadiyah 3 Yogyakarta. The results of the study are as follows. First, English education planning is prepared based on subjects, competency standards, basic competencies, learning objectives, teaching modules, procedures, time allocation, learning activities, learning resources/equipment, and evaluation of distance education students' learning outcomes during the Covid- 19. Second, the implementation of education that the teacher is trying has been guided by the latest updated syllabus and online learning implementation plan. English teachers have practised innovative education during the Covid-19 pandemic, such as Google Classroom, Zoom, WhatsApp, and many more. Distance learning that the teacher applies is to open lessons, deliver modules or teaching materials two days before learning activities occur, and discuss learning with students where learning is student-centred. The educational process places more emphasis on the cognitive and psychomotor domains. Third, learning assessment uses pre-test and post-test when online education takes place. The evaluation method used in learning applies direct observation, carries out tests/exercises at the end of the lesson so that the teacher knows the weaknesses and measurements of each student. Learning support facilities at Muhammadiyah 3 High School Yogyakarta are equipped with a language laboratory to facilitate the implementation of learning English more effectively.